2014
DOI: 10.3171/2014.2.peds13361
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management and long-term outcome of pediatric patients with different subtypes of epilepsy associated with cerebral cavernous malformations

Abstract: Object Sufficient data on surgical treatment and seizure outcome of pediatric patients with different types of epilepsy, especially drug-resistant epilepsy and associated cerebral cavernous malformations, are scarce. The aim of this study was to carefully evaluate seizure outcome using the International League Against Epilepsy (ILAE) classification with regard to the presurgical symptom duration. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Preoperative pyramidal tract visualization, which demonstrates the 3D positional relationship between the lesion and the pyramidal tract, helps the neurosurgeon develop an optimal surgical approach. Some studies have confirmed the importance of preoperative visualization of functional structures in surgical planning [5,6,14,15,17]. In this study, the entire pyramidal tract was successfully reconstructed preoperatively, showing the 3D positional relationship between the lesion and the pyramidal tract.…”
Section: Diagnosis and Surgical Indicationsmentioning
confidence: 56%
“…Preoperative pyramidal tract visualization, which demonstrates the 3D positional relationship between the lesion and the pyramidal tract, helps the neurosurgeon develop an optimal surgical approach. Some studies have confirmed the importance of preoperative visualization of functional structures in surgical planning [5,6,14,15,17]. In this study, the entire pyramidal tract was successfully reconstructed preoperatively, showing the 3D positional relationship between the lesion and the pyramidal tract.…”
Section: Diagnosis and Surgical Indicationsmentioning
confidence: 56%
“…19 In patients with longstanding recalcitrant seizures, there is a better likelihood of seizure control if hemosiderin surrounding the lesion can be removed safely, and when resection of adjacent mesiotemporal structures is performed in cases with temporal lobe epilepsy and associated memory dysfunction or hippocampal atrophy. 7,11,80,101 Recent reports suggest a role for laser fiber ablation of CAs as a potentially promising treatment of associated epilepsy. 104 There are conflicting data on resection of a DVA associated with CA, with most authors advocating DVA preservation to prevent serious complications such as edema, hemorrhage, and/or venous infarctions.…”
Section: Surgical Opportunities and Challengesmentioning
confidence: 99%
“…Twenty-eight patients presenting nonepileptogenic symptoms such as hemorrhagic focal neurologic deficits, seizure, and headache were excluded. This study was approved by the institutional review board of Fuzhou General Hospital (No.2017- [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Written informed consents were obtained from all patients and their guardians.…”
Section: Patientsmentioning
confidence: 99%